Pearl$1 (Bs passover :s a family celebration through stories, recipes, crafts, and songs - Zalben, Jane Breskin (New York : Simon & Schuster Books for Young Readers, 2002)
As an extended family prepares for their Passover celebration, they explain the various customs and traditions related to this holiday. Includes various related activities.
Keywords: Passover -- Fiction; Seder -- Fiction; Jews -- United States -- Fiction; Handicraft